2021
DOI: 10.1021/acs.macromol.1c01725
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired, Strong, and Tough Nanostructured Poly(vinyl alcohol)/Inositol Composites: How Hydrogen-Bond Cross-Linking Works?

Abstract: Spider silk-inspired hydrogen-bond (H-bond) cross-linking has recently been shown to enable polymers, e.g., poly(vinyl alcohol) (PVA), to achieve high strength in combination with large ductility and great toughness by adding small H-bond cross-linkers. Unfortunately, the correlation of H-bond cross-linking to the microstructure and mechanical performances of the resultant polymers remains unclear. Herein, we prepare strong and tough nanostructured PVA composites with inositol (IN) molecules as cross-linkers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…These characteristics suggested that the environment surrounding PVA was changed by the blending, in other words, at least a portion of PVA interacted with RHW via hydrogen bonds instead of strong hydrogen bonds within PVA. 52 For examining such an interaction, the hot-pressed PVA and hot-pressed RHW were pulverized and mixed manually at a mass ratio of 20:80 (referred to as the RHW/PVA20_mix), and the FTIR spectrum of the mixture was measured and compared with that of RHW/PVA20. As shown in Figure S7a , the absorption peak of the RHW/PVA20 composite shifted slightly to the higher wavenumber side (the region marked by a cycle showed a greater difference), and then the migration of PVA into the RHW matrix was confirmed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These characteristics suggested that the environment surrounding PVA was changed by the blending, in other words, at least a portion of PVA interacted with RHW via hydrogen bonds instead of strong hydrogen bonds within PVA. 52 For examining such an interaction, the hot-pressed PVA and hot-pressed RHW were pulverized and mixed manually at a mass ratio of 20:80 (referred to as the RHW/PVA20_mix), and the FTIR spectrum of the mixture was measured and compared with that of RHW/PVA20. As shown in Figure S7a , the absorption peak of the RHW/PVA20 composite shifted slightly to the higher wavenumber side (the region marked by a cycle showed a greater difference), and then the migration of PVA into the RHW matrix was confirmed.…”
Section: Resultsmentioning
confidence: 99%
“…The peak centers for RHW/PVA20 and RHW/PVA20/GL2 were very close to that for RHW. These characteristics suggested that the environment surrounding PVA was changed by the blending, in other words, at least a portion of PVA interacted with RHW via hydrogen bonds instead of strong hydrogen bonds within PVA . For examining such an interaction, the hot-pressed PVA and hot-pressed RHW were pulverized and mixed manually at a mass ratio of 20:80 (referred to as the RHW/PVA20_mix), and the FTIR spectrum of the mixture was measured and compared with that of RHW/PVA20.…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, more polar functional groups in T‐CNF form more hydrogen bonds with PVA, resulting in stronger interfacial force in the composites, thus the enhancement is higher than that of unmodified CNF. Thirdly, the abundant hydrogen bonds at the interface can reversible fracture/re‐construction when the composites are subjected to external loading, thus dissipating the energy and increasing the toughness of the composite, such mechanism was frequently been applied to improve the toughness of PVA in recent literatures 44–47 . These factors make the mechanical properties of T‐CNF/PVA composites improved comprehensively.…”
Section: Resultsmentioning
confidence: 99%
“…30 Inspired by this strategy, many new strong and tough self-healing materials have been developed utilizing hierarchical hydrogen bonds. [31][32][33][34] Adequate hydrogen bonds are broken upon stretching to dissipate input energy endowing materials with high ductility and toughness, while nanoconned phases as physical crosslinkers are attributed to the reinforced tensile strength. Although self-healing polymers have been developed with this concept, 5,35 tensile strength and stretchability are hardly up to 50 Mpa and 2500% elongation simultaneously.…”
Section: Introductionmentioning
confidence: 99%